Tingkat Partisipasi Masyarakat Dalam Pengelolaan Limbah Organik Pasar Raya MMTC - Halim, Jennifer; Syukri Hidayat; Irene Anggreny Br. Manik; Krisna Natalin Simbolon; Melinda Saragi; Windri Priskila Gultom (MARHALADO : Jurnal Pengabdian kepada Masyarakat, 2023)
This research focuses on the issue of organic waste management in Pasar Raya MMTC, which is a major contributor to the increasing amount of waste in Indonesia, especially in the market sector. The objectives of the study were to analyze the level of community participation in organic waste management, identify the constraints faced in organic waste management, and highlight the importance of organic waste management in Pasar Raya MMTC. This research used descriptive method with qualitative descriptive analysis. The results revealed that the low level of community participation in organic waste management in this market is due to the lack of facilities and education on proper waste management to traders and the community. Increased market activity has a significant impact on increasing the volume of organic waste, and without active community participation, waste management is not optimal. This research is expected to have a positive impact on the environment and public health by encouraging community awareness and participation in better organic waste management.